Ruptured Congenital Cholesteatoma Presenting as Atticoantral Chronic Suppurative Otitis Media in a 4-Year-Old: A Diagnostic Challenge - Made Lely Rahayu; I Gusti Ayu Mahaprani Danastri; I Nyoman Swardyana; Komang Soniananda Pradnyana Putri (Archives of The Medicine and Case Reports, 2026)
Chronic suppurative otitis media (CSOM) of the atticoantral type is a distinct otologic pathology driven by cholesteatoma, characterized by enzymatic bone erosion and a high risk of intracranial complications. While typically acquired through retraction pockets, a subset of these cases represents congenital cholesteatomas (CC) that have silently expanded and ruptured the tympanic membrane. This presentation mimics acquired disease, creating a diagnostic blind spot. We report the case of a 4-year-old male presenting with a one-year history of persistent, foul-smelling otorrhea and otalgia in the right ear. Despite a history of recurrent cold, there was no prior trauma or otologic surgery. Physical examination revealed an attic perforation with purulent discharge. Computed tomography scan (CT-scan) identified a soft tissue mass filling the epitympanum and mesotympanum with significant erosion of the scutum and ossicles. The patient underwent a modified radical mastoidectomy with type II tympanoplasty. Intraoperative findings revealed an extensive cholesteatoma sac consistent with a congenital origin that had secondarily ruptured. In conclusion, congenital cholesteatoma must be considered in the differential diagnosis of pediatric CSOM, even in the presence of a perforation. This ruptured presentation highlights the necessity of early HRCT imaging over conventional radiography. The canal wall down approach remains a critical strategy for eradicating extensive pediatric disease to prevent recidivism.